Voluntary information and price sharing database – a scoping review of the pricing and procurement landscape across eight Commonwealth Member States - Bridget Kebirungi; Phyllis Ocran; Nduta Kamere; Lynette Keneilwe Mabote; Ngozi Osi; Meghna Joshi-von Heyden; Emily Gilmour; Janneth Mghamba; Layne Robinson; Zaheer-Ud-Din Babar; Helena Rosado; Victoria Rutter (Journal of Pharmaceutical Policy and Practice)
Background The Commonwealth Health Ministers’ meetings (2021–2023) identified medicines shortages, pricing, and price transparency as critical issues. This led to the establishment of the Voluntary Information and Price Sharing Database (VIPSD) in 2021, aimed at enhancing procurement transparency, reducing costs, and sharing information on health products amongst member states. However, adoption has been limited due to competing initiatives like pooled procurement systems introduced during the pandemic.Methods This scoping review focused on eight Commonwealth countries: Bangladesh, Dominica, Kenya, Malaysia, Malta, Solomon Islands, South Africa, and St. Vincent and the Grenadines. Nations were selected to represent diverse health systems, population sizes, and procurement practices. External researchers conducted literature reviews and standardised data collection to ensure consistency.Results The review revealed varied pricing policies and procurement frameworks. Nations like Malta, Bangladesh, Malaysia, and South Africa had pharmaceutical policies ensuring affordability, while others lacked comprehensive pricing policies. Seven countries implemented pooled procurement programmes, enhancing value and reducing costs; three nations operated national health insurance schemes affecting medicine pricing. Five countries used pharmaceutical management information systems to streamline procurement. Despite these efforts, disparities persist due to fragmented frameworks, stock-outs, budget constraints, and delayed procurement processes.Conclusion The VIPSD was identified as a potentially transformative tool to enhance transparency, promote fair pricing, improve collaboration, and ensure equitable access to innovative health products. To maximise its impact, the database requires clear scope definition, comprehensive data collection, funding, and robust maintenance. Expanding its adoption could help mitigate price disparities and strengthen medicine accessibility across Commonwealth member states.